Analisis Hubungan Antar Manusia Dan Lingkungan Kerja Fisik Terhadap Etos Kerja Karyawan Perumda Air Minum Tirta Jaya Mandiri Kabupaten Sukabumi - Sandra Dwi Pratiwi; Acep Samsudin; Asep Muhamad Ramdan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This research was carried out with the aim of knowing the description of the relationship between humans, the physical work environment, and the work ethic of the employees of Perumda Air Drinking Tirta Jaya Mandiri, Sukabumi Regency. This study also aims to determine the effect of the relationship between humans and the physical work environment on the work ethic of the employees of Perumda Airminum Tirta Jaya Mandiri, Sukabumi Regency. Researchers used descriptive and associative research methods with a quantitative approach and distributed questionnaires to 58 respondents, namely employees of Perumda Water Drinking Tirta Jaya Mandiri, Sukabumi Regency. The research data analysis used was validity test, reliability test, normality test, correlation technique analysis, coefficient of determination analysis, multiple linear analysis, and hypothesis testing, namely T test and F test. The results showed that the relationship variables between humans and the physical work environment had a relationship. which is strong with a work ethic variable that is equal to 0.874. The results of hypothesis testing also show that the relationship between humans and the work environment has a positive and significant influence on the work ethic of the employees of Perumda Airminum Tirta Jaya Mandiri, Sukabumi Regency. Keywords : Human Relationship, Physical Work Environment, Work Ethic